Relationships of CRP and P Wave Dispersion With Atrial Fibrillation in Hypertensive Subjects - Tsioufis, Costas; Syrseloudis, Dimitris; Hatziyianni, Awalia; Tzamou, Vanessa; Andrikou, Ioannis; Tolis, Panaglotis; Toutouzas, Kostas; Michaelidis, Andreas; Stefanadis, Christodoulos (American journal of hypertension, 2010)
Background Although inflammation has been shown to be implicated in the pathophysiology of atrial fibrillation (AF), little is known about its involvement in the accompanying atrial electrical remodeling expressed by P wave dispersion (Pdisp). Methods Fifty hypertensive subjects with documented paroxysmal AF (AF group) and 50 matched for body mass index, sex and office systolic blood pressure (BP) subjects with no history of AF (SR group) were subjected to electrocardiogram (ECG) and Pdisp assessment, hs-CRP determination, a complete echocardiographic study and 24-h ambulatory BP monitoring. Results The AF as compared to the SR subjects were older by 14 years (P < 0.0001) and they exhibited lower office and 24-h diastolic BP (7mmHg, P < 0.0001 and by 8mmHg, P < 0.0001, respectively) and higher office and 24-h pulse pressure (by 4mmHg, P = 0.03 and 6mmHg, P = 0.001, respectively) mean values. A higher mean of left atrial (LA) diameter index (by 1.9mm/m2, P < 0.0001) and left ventricular mass index (by 16g/m2, P < 0.0001) were observed in the AF vs. SR group. Pdisp mean and hs-CRP median values were higher in the AF group (by 22ms, P < 0.0005 and by 4.63mg/l, P < 0.0005, respectively). Standard multiple and multiple logistic regression analysis identified log10(hs-CRP) as independent determinant of Pdisp and log10(CRP) and Pdisp as independent determinants of AF. Conclusions In hypertensive subjects hs-CRP and Pdisp are interrelated and associated with AF, suggesting an active implication of inflammation in the atrial electrophysiological remodeling predisposing to AF.